Impact of ascophyllum marine plant extract powder (AMPEP) on the photosynthesis of Eucheuma denticulatum (Rhodophyta) from tissue culture. - Valera, Jeane Valerie P.
Ascophyllum Marine Plant Exract Powder (AMPEP) is a seaweed-derived extract that contains bioactive compounds that contribute benefits to the agriculture, horticulture, and animal feed. The mechanisms behind its efficacy as a biostimulant and its mode of activity in influencing algal photosynthesis, have not yet been extensively explored. In this study, the effects of AMPEP on photosystem II (PSII) photochemical efficiency of tissue-cultured Eucheuma denticulatum subjected to different salinities (10, 20, 30, 33, 40, 50, and 60 psu), combined temperature (26, 30, 34â„ƒ) and irradiance (200 and 1000 Î¼mol photons mâ»Â² sâ»Â¹), and temperature gradients (10, 14, 18, 22, 26, 30, and 34â„ƒ) were investigated using a pulse amplitude modulation (PAM)-fluorometer. Results showed that there was no significant difference on the maximum quantum yields (Fáµ¥/Fâ‚˜) between the AMPEP-treated samples (0.0547 Â± 0.060 - 0.55496 Â± 0.105) and control (i.e., without AMPEP; 0.065 Â± 0.059 - 0.5516 Â± 0.163) for all salinities. Both treatment and control groups of E. denticulatum exhibited a euryhaline characteristic, tolerating salinities ranging from 20 to 50 psu. The effective quantum yields (â–³F/Fâ‚˜â€²) of the AMPEP-treated algal samples at 6-hour exposures to 26â„ƒ, 30â„ƒ, and 34â„ƒ under high and low irradiance showed photoinhibition but to a lesser extent compared to the control; partial recovery in their â–³F/Fâ‚˜â€² following overnight dark acclimation also occurred. High Fáµ¥/Fâ‚˜ were observed at 26 to 30â„ƒ, but gradually declined beyond such temperatures in AMPEP-treated E. denticulatum. Overall, the present study provides evidence of the efficacy of AMPEP by enhancing the photosynthetic performance of E. denticulatum under abiotic conditions, notably to temperature and irradiance stressors.